Human TRIM5alpha expression levels and reduced susceptibility to HIV-1 infection - Sewram, Shamman; Singh, Ravesh; Kormuth, Emil; Werner, Lise; Mlisana, Koleka; Karim, S S Abdool; Ndung'u, Thumbi (The Journal of infectious diseases, 2009)
Human TRIM5alpha (TRIM5alphahu), a member of the tripartite motif protein family, displays some anti-human immunodeficiency virus type 1 (HIV-1) activity in vitro, although it is substantially less potent than its rhesus monkey counterpart (TRIM5alpharh). The effects of levels of TRIM5alphahu on prevention or control of HIV-1 infection in vivo are unknown. We used a quantitative real-time polymerase chain reaction (PCR) assay to measure levels of TRIM5alphahu expression in peripheral blood mononuclear cells (PBMCs) obtained from a cohort of individuals at high risk for HIV-1 infection in Durban, South Africa. Samples were available from 38 infected subjects (with all these samples obtained within 1 year of infection) and from 57 uninfected persons. Matched preinfection and postinfection samples were available from 13 individuals. TRIM5alphahu messenger RNA levels were lower in the PBMCs of HIV-1-infected subjects than in those of uninfected subjects (P <.001). Seroconverters had lower preinfection levels of TRIM5alphahu than did nonseroconverters (P<.001). TRIM5alphahu levels did not change significantly after infection. There was no correlation between TRIM5alphahu levels and viral loads or CD4(+) T cell counts. High expression of TRIM5alphahu is associated with reduced susceptibility to HIV-1 infection. Furthermore, infection is not associated with disregulation of TRIM5alphahu. TRIM5alphahu expression levels do not contribute to the control of primary HIV-1 viremia.